EFFECT BETWEEN ENTERPRISE VALUE AND DIVIDEN POLICY - Putra, Raditya Koesdijarto (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
In this paper researcher aims to fill gap in the literature about correlation of enterprise value with dividen policy and investment behavior. This paper uses systematic literature review. The literature used by the author comes from books that are appropriate to the topic, international and national journals published. The writing results obtained are topics about enterprise value with dividen policy and investment behavior which have been discussed in many reviews of methods and viewpoints, with mixed results. The results of research using quantitative methods with significant and insignificant results, when using qualitative methods, there are results of implementation that are appropriate and not in accordance with the rules that should be.